2018
DOI: 10.7554/elife.34031
|View full text |Cite
|
Sign up to set email alerts
|

Forniceal deep brain stimulation induces gene expression and splicing changes that promote neurogenesis and plasticity

Abstract: Clinical trials are currently underway to assess the efficacy of forniceal deep brain stimulation (DBS) for improvement of memory in Alzheimer’s patients, and forniceal DBS has been shown to improve learning and memory in a mouse model of Rett syndrome (RTT), an intellectual disability disorder caused by loss-of-function mutations in MECP2. The mechanism of DBS benefits has been elusive, however, so we assessed changes in gene expression, splice isoforms, DNA methylation, and proteome following acute forniceal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 89 publications
4
33
0
Order By: Relevance
“…This new DBS apparatus allows unrestricted moving and feeding of experimental animals and delivers long-term chronic stimulation (at the effective voltage for over 3 months), which is more advantageous than the majority of previous DBS devices used for rodent models ( 32 , 33 ). We have observed that HF-DBS increases the expression of activity-dependent genes c-fos and Npas4 in the AI, which suggests our stimulation protocol modulates AI cellular activity and is in line with previous DBS studies ( 34 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…This new DBS apparatus allows unrestricted moving and feeding of experimental animals and delivers long-term chronic stimulation (at the effective voltage for over 3 months), which is more advantageous than the majority of previous DBS devices used for rodent models ( 32 , 33 ). We have observed that HF-DBS increases the expression of activity-dependent genes c-fos and Npas4 in the AI, which suggests our stimulation protocol modulates AI cellular activity and is in line with previous DBS studies ( 34 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…We identified that latestage CLN3 -/mice, like several mouse models of AD, have a decrease in the absolute number of hippocampal SWRs, a physiologic oscillation important for memory consolidation (31)(32)(33). Identification of shared network features could motivate future studies of network-targeted therapies, which are under development for AD (45)(46)(47)(48), in CLN3 disease. Studies of hippocampal-mediated learning and memory in CLN3 -/mice across the life span are needed to fully characterize the impact of these network alterations.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study reported an increase in NPCs in the SVZ associated with subthalamic nuclei DBS in patients with Parkinson's disease 35 . Preclinical studies have also demonstrated anti-epilepsy effects, antidepressant/anxiolytic responses and memory improvements by DBS correlated with neurogenesis [36][37][38] . Even so, adult neurogenesis is very species-specific, and the occurrence of neurogenesis in humans needs more critical thinking.…”
Section: Discussionmentioning
confidence: 98%